KAJIAN MODEL SPRINGATE PADA KELOMPOK SAHAM JAKARTA ISLAMIC INDEX PERIODE 2013 – 2017 - Anggara, Windu (IAIN Langsa, 2019)
This study aims to find out and analyze the health condition of the company based on the magnitude of the predicted value using financial ratios in the Springate model. The research method used is descriptive analysis method with a quantitative approach. The research population is all companies listed in Jakarta Islamic Index (JII), amounting to 30 companies, using purposive sampling. The analysis technique used is the analysis of financial statements with the Springate model (S-Score) which aims to find out companies that experience financial distress and bankruptcy. The results showed that there were several companies in 2013 and 2014 that experienced bankruptcy, namely 16.67%, then increased to 26.67% in 2016, and the most significant occurred in 2015 and 2017, namely 30.00%.